Facile conversion and eco-friendly carbon-bentonite nano sheets synthesis from waste PET bottles and application in Cr6+ removal from aqueous solution - Sahragard, Sepideh (Environmental technology, 2025)
Plastics are extensively utilised in all aspects of life owing to their durability and low price. Global production of polyethylene and polypropylene (the most common microplastics in soil and water) is increasing at an annual rate of approximately 7%. However, owing to the weak plastic natural degradation, low recycling rate, and potential ecological and health risks, the environmental issues brought on by plastic accumulation in marine and land environments have garnered international attention. To protect the environment, waste minimisation, reuse, and recycling processes should be developed. However, heavy metals such as chromium have caused many problems in aquatic environments. This study mainly aimed to synthesise carbon-bentonite nanocomposite and its use for chromium removal. The aforementioned nanocomposites were characterised by FESEM, XRD, EDX, FT-IR, and DLS techniques. To explore the mutual effects of various parameters in chromium adsorption, Central Compound Design (CCD) and Response Surface Methodology (RSM) were used. The maximum efficiency of chromium removal at pH of 5, 90 (minutes), initial chromium concentration of 20 (mg/L), and adsorbent dosage of 10 (mg/L), which was equal to 46.17% and adsorption capacity = 16.5 mg/L. Based on findings, chromium adsorption followed pseudo-second-order (PSO) kinetics and Freundlich and Langmuir isotherms. Thermodynamic and temperature studies also demonstrated that the process efficiency increased with increasing temperature. Owing to its availability and low cost, the combination of nano-bentonite and carbon obtained from PET recycling is recommended as a good adsorbent for removing chromium and other pollutants